Growth, condition factor, maturity, gonadal development and spawning of fork-tail threadfin bream (Nemipterus furcosus) in the Coastal Water of Pahang - Samad, Amira Farzana; Rahman, Mohammad Mustafizur; Saad, Shahbudin (2013)
Fork-tail threadfin bream (Nemipterus furcosus) is an economically important food fish in Malaysia but the capture production of this fish is decreasing gradually in the Malaysian water. However, nothing is known about the population of this species in the Malaysian water especially in the coastal of Pahang. Therefore, this research aimed to understand some important characteristics of fork-tail threadfin bream population in the coastal water of Pahang. For this study, monthly samples were collected from commercial fishing trawlers for a period of one year (August 2012 - July 2013). A total of 1531 threadfin bream specimens were studied in this research. The results showed that male threadfin bream was significantly more than female (2 = 108.05; p<0.05) in the population of Pahang coastal water. Length-weight relationship of each month was significant (p<0.05) with all coefficients of determination (R2) values being higher than 0.73. The growth coefficient (b value) varied between 2.307 (May) and 3.1731 (October). A negative allometric growth of threadfin bream was observed in all months except October when a positive allometric growth was observed. The growth coefficients was very low in September for female and in May for male compared to other months. The significantly (P<0.05) lowest mean condition factor was found in May (2.7004) and the highest in January (2.9054) and August (2.9249). Overall higher mean condition factor was observed in smaller fish of both sexes. The overall mean condition factor of female was better than male. Gonadosomatic index of female threadfin bream was highest in June while male in November. Gonadosomatic index of female rapidly increased after December and reached at peak in June and decline after June. The peak spawning season of threadfin bream in Kuantan coastal water was from Jnuary to August. The results of the proposed study will help the management of juvenile and breeding fork-tail threadfin bream stock in order to maintain sustainable exploitation in the coastal water of Pahang.